PEMBELAJARAN KEWIRAUSAHAAN MELALUI KUNJUNGAN USAHA: STUDI KASUS PADA USAHA YARA CAPPUCINO ALUMNI - Muhammad Rangga Wibiksana; Muhammad Fariz Abdullah Pelu; Amanda Tri Utami (Media Resonansi Pengabdian Masyarakat, 2025)
The alumni business visit activity is part of practical learning to get to know the world of entrepreneurship directly. Through a visit to the alumni's "Yara Cappucino" business, students gain an understanding of how to build and manage a small business in the beverage sector. This research was conducted in three stages of visits to explore information related to the business background, operational strategies, and financial aspects. The results of this activity show that despite facing various challenges such as weather and limited promotion, businesses can survive and grow with an entrepreneurial spirit and creativity. This activity provides valuable learning related to the reality of building a business from the bottom and the importance of innovation and proper management.Keywords: business visits, entrepreneurship, MSMEs, contemporary drinks, Yara Cappuccino.